An experiment with PBL in higher education as appraised by the teacher and students - Luis Roberto de Camargo Ribeiro (Interface: Comunicação, Saúde, Educação, 2005)
PBL (Problem-based Learning) has gained worldwide acceptance as an effective instructional approach that helps students to acquire knowledge as well as develop desired professional skills and attitudes. Contrary to other conventional methods that use problems after theory has been introduced, PBL uses a problem to initiate, focus and motivate the learning of new concepts. This paper presents and discusses the students' and the teacher's viewpoints on the implementation of PBL in an Administration Theory course of an engineering curriculum at a public university in Brazil. The data were collected by means of unstructured interviews, participant observation and an open-ended questionnaire responded by the students at the end of the course. The results show that despite increasing the workload for the teacher and the students, both evaluated PBL positively because it is more motivating and dynamic.